2020
DOI: 10.20525/ijrbs.v9i5.854
|View full text |Cite
|
Sign up to set email alerts
|

Influence of employer-employee relationships on service quality in the hospitality industry in Nakuru County, Kenya

Abstract: Employees are the backbone of the hospitality industry, and the people in service are inseparable from the service they provide. This research investigated the influence of employer-employee relationships on service quality in the hospitality industry in Nakuru County, Kenya. Descriptive design was used to gather both quantitative and qualitative data through the use of questionnaires and interview guide as the key informants. The target population was 73 respondents comprising of 55 employees’ operational emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Since the results show that all three aspects of engagement are significantly related to employee job performance, this suggests that highly engaged employees can perform their jobs more competently and successfully (Rana et al 2019). The quality of the employeremployee relationship determines how committed employees are to their work (Mburu et al 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the results show that all three aspects of engagement are significantly related to employee job performance, this suggests that highly engaged employees can perform their jobs more competently and successfully (Rana et al 2019). The quality of the employeremployee relationship determines how committed employees are to their work (Mburu et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The employment relationship is the existence of a link between an employer and an employee within an organisation (Arimie 2019). Managers and supervisors have come to be seen as servant leaders who provide a comfortable working environment for their employees, instead of the "bosses" of the past (Mburu et al 2020).…”
Section: Concepts Of the Employment Relationshipsmentioning
confidence: 99%
See 1 more Smart Citation
“…EE is a necessity for businesses because of its favourable impact on employee, team, and organizational outcomes (Bakker & Albrecht, 2018), and it is a way to enhance strategy implementation and decrease performance gaps and waste (Nienaber & Martins, 2020;Katili, Wibowo, & Akbar, 2021) in an organization. It is also a recipe for positive overall performance of an organization (Sutisna, Fauziya, & Pranoto, 2020), and can thus be a game changer in organizational performance (Mburu, Koome, & Gichuhi, 2020) in this current business environment. In light of that, Jabeen & Rahim (2021) concluded that the financial and non-financial outcomes of an organization are highly dependent on the performance of its employees.…”
Section: Introductionmentioning
confidence: 99%
“…There is no doubt that EE is a necessity for businesses because of its favorable impact on teams, organizational output, and employees (Bakker & Albrecht, 2018), and it is a way to enhance strategy implementation and decrease performance gaps and waste (Katili et al, 2021; Nienaber & Martins, 2020) in an organization. It is also a recipe for positive overall performance in an organization (Sutisna et al, 2020) and can, thus, be a game changer in organizational performance (Mburu et al, 2020) in this current business environment.…”
Section: Introductionmentioning
confidence: 99%